Humor and personality : temperament and character have different roles - Moreira, Paulo (2022)
This study aimed to test how sense of humor is dependent on the complex and dynamic interactions between the emotional (temperament) and sociocognitive (character) components of personality. Specifically, we examined the relationship of temperament and/or character profiles to overall humor potential and comic style. In total, 665 adults responded to Cloninger’s Temperament and Character Inventory (TCI) and the Comic Style Markers. Temperament profiles were associated with overall humor potential but not comic styles. People with positive development of all three character traits had the highest levels of fun, benevolent humor, and wit. Sense of humor depended on integrated profiles of both temperament and character. We conclude that temperament energizes overall humor potential while character shapes the comic styles. This study advances research by directing focus to the causal within-person psychobiological processes that underlie sense of humor.